Leadership and resilience at the Islamic University of Gaza, 1978-2012 - EL-Namrouti, Said Ahmed (My University, 2016)
Leadership in Higher Education Institutions (HEIs) in turbulent times has been undertheorised. A qualitative case study based on document analysis of 70 documents, 39 interviews and 2 focus groups was the vehicle for examining the role of the leadership at the Islamic University of Gaza (IUG). IUG has operated under complex conditions of occupation and ongoing turbulence from its inception in 1978 to the present. This study examines the period 1978-2012. In this time the university grew from 25 men studying Sharia in a tent to 20,000 students (63.7% female) studying across 11 faculties and 112 different specialisations. The study documents and labels four phases of development of the university. The patterns of leadership uncovered in the study include transformational, transactional, heroic, post-heroic and on some specific occasions authoritarian styles, with transformational being the most important. The way in which the leadership resolved short term crises, as well as their long-term and big-picture focus, shaped the development of the university. Resilience theory was applied alongside leadership theory to analyse the responses of IUG leadership. Resilience was taken beyond surviving to capitalising on disruption. Twenty three markers of resilience were found which worked independently and interactively to support resilient responses to the challenges IUG faced. These factors were initially developed from the literature, and new factors were added based on this research. The relationship between leadership styles and the promotion of resilience was examined. The thesis describes a mutual shaping and supporting role between university and society in Gaza, and discusses some of the paradoxes of help and harm coming from players and belief systems external to the university. The paradox of faith which can provide a cohesive, binding set of beliefs to support staff and students, as well as being the source of conflict and harm, is also discussed. A definition of a university as an educational community functioning beyond place, buildings, external recognition, or physical destruction was developed.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management The University of the Witwatersrand, Johannesburg, 2017
Keywords: Islam; Islamic countries--Politics and government